Does the Welfare State Affect Individual Attitudes toward Immigrants? Evidence across Countries - Facchini, Giovanni; Mayda, Anna Maria (The Review of Economics and Statistics, 2009)
This paper analyzes welfare-state determinants of individual attitudes toward immigrants—within and across countries—and their interaction with labor market drivers of preferences. We consider two mechanisms through which a redistributive welfare system might adjust as a result of immigration. Under the first model, immigration has a larger impact on high-income individuals, while under the second one low-income individuals are those most affected. Individual attitudes are consistent with the first welfare-state model and with labor market determinants. In countries where immigration is unskilled, income is negatively correlated with pro-immigration preferences, while skill is positively correlated with them. These relationships are reversed in economies characterized by skilled migration.